Do espaço lembrado ao espaço vivido: narrativas orais de mulheres nordestinas em Parintins-AM, na segunda metade do século XX - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
Migration is a complex, plural and interdisciplinary event, because it is imbued with, spatial, symbolic, cultural, affective elements and especially of meanings that marked the lives of the individuals involved in their migratory processes. The development of this study contributes to the construction of a new historiographical view about the construction of a new historiographical view about the Northeastern migration to the region highlighting the experiences of eight northeastern women in the second half of the 20th century. Beside understanding the role played by women in this context, especially in the Brazilian Amazon though migratory movements between the northeast and north, contributing significantly in the social landscape of the north. Since it points out woman as an active subject in the social dynamics with to possible ruptures and permanences in the referred period, during her experiences inside the Amazon. To understanding the migratory process of cache northeastern woman and to construe the senses attributed by them to their trajectories is one of the objectives outlined that it is possible to perceive the conceptions changes linked to possible conflicts and mobilizations by the actions of these woman. The affectivity involved in the process of each one is shown as a fundamental and decisive element for their exit to the northeast. In this way, we understand that the migration flow happens at different times and reasons. The historical construction of this theme walks intertwined with the history, memory and time narrated by them, and this, carries within it sef the ruptures, permanences and continuities that cross the experiences of each Northeast woaman.
Keywords: Migração; Mulheres Nordestinas; Migração nordestina; CIÊNCIAS HUMANAS: HISTÓRIA